Evaluating the anticancer activity and nanoparticulate nature of homeopathic preparations of Terminalia chebula - Wani, Kirtee; Shah, Nilesh; Prabhune, Asmita; Jadhav, Arun; Ranjekar, Prabhakar; Kaul-Ghanekar, Ruchika (Homeopathy, 2016)
Background: Breast cancer is the most common cancer diagnosed among women and is the second leading cause of cancer death. Homeopathic medicines are part of the alternative medicines that are given as a supportive therapy in breast cancer. The objective of this study was to investigate the anticancer activity of commercially available homeopathic preparations of Terminalia chebula (TC) and evaluate their nanoparticulate nature. Methods: Mother tincture (MT) and other homeopathic preparations (3X, 6C and 30C) of TC were tested for their effect on the viability of breast cancer (MDAMB231 and MCF7) and non-cancerous (HEK 293) cell lines by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Cell growth assay was performed to analyze the effect of the different potencies on the growth kinetics of breast cancer cells. MT and 6C were evaluated for the presence of nanoparticles by using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Results: MT decreased the viability of breast cancer (MDAMB231 and MCF7) and non-cancerous (HEK 293) cells. However, the other potencies (3X, 6C and 30C) decreased the viability of only breast cancer cells without affecting the viability of the non-cancerous cells. All the potencies, MT, 3X, 6C and 30C, reduced growth kinetics of breast cancer cells, more specifically at 1:10 dilution at 24, 48 and 72 h. Under SEM, MT appeared as a mesh-like structure whereas under TEM, it showed presence of nanoclusters. On the other hand, 6C potency contained 20 nm sized nanoparticles. Conclusion: The current study reports the anticancer activity of homeopathic preparations of TC against breast cancer and reveals their nanoparticulate nature. These preliminary results warrant further mechanistic studies at both in vitro and in vivo levels to evaluate the potential of TC as nanomedicine in breast cancer.